If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x = 36x Solving 8x = 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 8x + -36x = 36x + -36x Combine like terms: 8x + -36x = -28x -28x = 36x + -36x Combine like terms: 36x + -36x = 0 -28x = 0 Divide each side by '-28'. x = 0 Simplifying x = 0
| 500-335= | | 48t^2-28t+2=0 | | 2x^2+10x=-6 | | -41=-2-13n | | 0=36p^2-31 | | 4x*2+8x-32=0 | | 0=36p^2-9 | | 40=36p^2-9 | | 9x*2-21=0 | | (x-4)(x+8)=64 | | -13+y=-24 | | 13+y=-24 | | -13y=-24 | | 6x^3+4x=10x^2 | | 5x-7=3x-10 | | 5x+24(x-4)=107 | | 4x-3+2x=8x | | 6+k=14 | | (2x^2+3x-2)(3x^2-6x-5)= | | n-4=24 | | 23=-2(24-b)+3(b-3) | | 15x+21(x-2)=318 | | 4x^2+7-3=0 | | 19x-(4x-9)=84 | | 19x-3(4x-9)=84 | | 5m+10=9m-2 | | 5(6z+1)-9=146 | | 3(4x-1)=36 | | (-6)(9)= | | (4-9)= | | 4w^2=-12w-5 | | [10-2]= |